Hyponatremia Is Associated With Post-thrombolysis Hemorrhagic Transformation and Poor Clinical Outcome in Ischemic Stroke Patients - He, Ling; Guo, Zhen-Ni; Qu, Yang; Jin, Hang (Frontiers in Molecular Neuroscience, 2022)
Objective Hyponatremia is the most common electrolyte disorder encountered in patients with neurological conditions, such as stroke. Studies have shown that it is associated with worse clinical outcomes and increased mortality in acute ischemic stroke (AIS). However, the role of hyponatremia has not been elucidated in patients with AIS who received intravenous thrombolysis (IVT) therapy. Therefore, this study aimed to investigate the effect of serum sodium levels on the clinical outcome and hemorrhagic transformation (HT) in patients with AIS who received thrombolytic therapy. Methods Patients diagnosed with AIS who received IVT therapy between May 2015 and December 2020 were included in this study. All patients were screened for serum sodium levels immediately after hospital admission, before IVT therapy. The occurrence of HT was evaluated using computed tomography (CT) 24 ± 2 h after thrombolysis. Then, 3-month clinical outcomes were obtained by telephone calls or outpatient visits, and poor 3-month clinical outcomes were defined as modified Rankin Scale scores ≥3. The effects of serum sodium levels on the clinical outcome and HT were assessed using the multivariate logistic regression analysis. Results Of the 963 included patients, 82 (8.5%) had hyponatremia, 157 (16.3%) developed HT, and 333 (34.6%) had poor 3-month outcomes. Of the 82 patients with hyponatremia, 21 (25.6%) developed HT, and 39 (47.6%) had poor 3-month outcomes. Patients with hyponatremia had a higher incidence of post-thrombolysis HT (25.6 vs. 15.4%, p = 0.017) and worse clinical outcome (47.6 vs. 33.4%, p = 0.01) than those with normal serum sodium levels. Patients had significantly lower serum sodium levels in those with HT [138.4 (136.4–140.3, IQR) vs. 139.0 (137.2–140.7, IQR) mmol/L, p = 0.019] and poor 3 month outcome [139.0 (137.2–140.7) vs. 138.4 (136.7–140.3) mmol/L, p = 0.005] than those without. After adjusting for major covariates, the multivariate logistic regression analysis revealed that lower serum sodium levels were independently associated with an increased risk of HT [odds ratio (OR) = 1.804; 95% CI: 1.048–3.105] and poor 3-month outcome (OR = 1.647; 95% CI: 1.012–2.679). Conclusion Lower serum sodium level was an independent risk factor for post-thrombolysis HT and poor clinical outcome in patients with AIS who received thrombolytic therapy.